Association between the dietary inflammatory index and depressive symptoms in adults with cardiovascular–kidney–metabolic syndrome: evidence of metabolic syndrome as a mediator - Tian, Ruo-Nan; Zhang, Sheng-Xiao; Zhang, Nan; Wu, Wen-Jing; Guo, Hua-Qing; Wang, Chen; Duan, Zhi-Guang (Frontiers in Nutrition, 2025)
BackgroundThis study aims to investigate the association between the dietary inflammatory index (DII) and depressive symptoms (Deps) in adults with cardiovascular–kidney–metabolic (CKM).MethodsUsing data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2005 to 2018, we examined the association between DII and Deps in CKM patients. We employed weighted multivariate logistic regression, generalized additive models, and restricted cubic spline models. Threshold effect analysis was performed to identify the inflection point in the smooth curves. Subgroup and sensitivity analyses were conducted to validate the robustness of the findings. Additionally, we used the Bootstrap method to evaluate the mediating role of metabolic syndrome (Mets).ResultsA total of 12,980 participants were included, with 1,096 (8.4%) identified as experiencing Deps. DII was associated with the risk of Deps, which remained robust after adjusting for 20 potential confounders. Specifically, each unit increase in DII was associated with an 18.7% higher incidence of Deps. The relationship between DII and Deps in CKM patients exhibited a J-shaped pattern, with a non-linear positive correlation observed in the Non-advanced CKM population. Subgroup analyses confirmed the correlation. Additionally, Mets mediated 4.44% of the observed effect.ConclusionThe DII was non-linearly associated with the risk of Deps in CKM patients. This highlights the importance of targeted interventions to address this comorbidity and mitigate the disease burden associated with both Deps and CKM syndrome.